Da cláusula de não-concorrência no contrato individual de trabalho - Novo, Catia Guimarães Raposo (2007)
With economic globalization and new technologies, know-how and researches developed became more relevant for the economic development of the societies. In addition to the capital and to labor, knowledge became an essential factor in the manufacturing process and generation of wealth, which in this new economic model ensures a company´s competitiveness and, in many cases, its own survival. The aforementioned changes have an impact on the working relationships as the inclusion of specialized employees in strategic areas of the company, including their access to privileged knowledge and information brought the need of new demands for regulating the employment agreement. Notwithstanding the foregoing, the inclusion of the non-competition clause in the employment agreement generates, theoretical deadlocks because it covers a period subsequent to the end of the employment relationship and addresses antagonic interests, particularly, the exercise of full employment in opposition to the property. Furthermore, this discussion covers the issue of the free will principle (autonomia da vontade) vis-à-vis the protectionism typical of the employment agreement. Therefore, considering the lack of laws regulating this theme, this study examines the applicability and prerequisites for the enforceability of the non-competition clause in the Brazilian law system, taking into account historic aspects; principles guiding the employment relationship; and those regulating agreements in general, compared right and the parties´ interest in including this clause. In short, after the analysis of the aforementioned topics, the conclusion was that the non-competition clause included in the employment agreement is an important instrument to safeguard the rights of both parties: employers and employees, and an applicable alternative to prevent conflicts related to manufacturing forms, management of knowledge and business competition practices